2010
DOI: 10.1111/j.1471-0528.2010.02548.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the relationship between maternal cardiac output measured by impedance cardiography and uterine artery blood flow in the second half of pregnancy

Abstract: Objective To study serial changes in maternal systemic and uterine artery haemodynamics and establish reference ranges for the second half of pregnancy.Design Prospective longitudinal observational study.Setting University hospital in Norway.Population Low-risk pregnant women.Methods Fifty-three low-risk pregnancies were evaluated at approximately 4-weekly intervals. Maternal systemic haemodynamics was assessed with impedance cardiography. Uterine artery blood velocity and diameter were measured using Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 35 publications
4
46
0
2
Order By: Relevance
“…The demographic and clinical characteristics of women included in the longitudinal arm of the study have been reported previously. [3] Briefly, all the 53 participants were healthy women, and none of them developed any significant pregnancy complications. Follow up data on the course of pregnancy and perinatal outcome were available for all the participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The demographic and clinical characteristics of women included in the longitudinal arm of the study have been reported previously. [3] Briefly, all the 53 participants were healthy women, and none of them developed any significant pregnancy complications. Follow up data on the course of pregnancy and perinatal outcome were available for all the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-three healthy pregnant women were recruited to the longitudinal arm of the study [3]. Blood samples were obtained serially between 22 and 40 weeks of gestation at approximately 4-weekly intervals (a total of 243 samples).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An electronically pivotable bed designed for changing position without any active movement by the study participant was used. Hemodynamic parameters were measured using impedance cardiography (ICG) (Phillips Medical Systems, Androver, MA, USA) as described previously [24]. Baseline measurements were obtained after approximately 10 minutes of rest in a supine recumbent position with the upper part of the bed at a 45° tilt.…”
Section: Methodsmentioning
confidence: 99%
“…The hormonal and hemodynamic changes in the peripartum, delivery, and post-partum period may account for the association between SCAD and post-partum status. Hormonal changes during pregnancy have been shown to have effects on the arterial wall, possibly predisposing to dissection in the coronary vasculature, in conjunction with the increased cardiac output that occurs throughout pregnancy and especially during delivery (104–106). …”
Section: Scadmentioning
confidence: 99%